Book of Beasties: Championing mental health in schools - Annita Ventouris; Michelle Jayman (University of West London, 2020)
School leaders need to be better supported to make informed decisions about strategies to promote mental health and to help pupils who are experiencing difficulties. One tool for doing this is 'Book of Beasties: The mental wellness card game'. Book of Beasties (BoB) is a mental wellness card game targeted at primary school children. It is underpinned by the belief that every child should have the confidence to talk openly about their emotions and mental health. BoB aims to de-stigmatise mental health, promote wellbeing and raise emotional literacy.